Zależność między okresem konwersji gotówki a rentownością – wyniki badań - Stefański, Artur (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The research covered 2012 and was based on the sample of 642 small and medium – sized enterprises. The negative correlation between cash conversion cycle and profitability was observed, also the positive weak correlation between inventory turnover ratio and profitability was stated.